2012
DOI: 10.2478/v10044-012-0001-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of psychological stress on skin and hair pigmentation in Polish adolescents

Abstract: The effects of psychological stress, gender and age on hair and skin pigmentation levels were evaluated in the reported study. The material included Polish high-school and university students aged 18-22 (in the age range 17.50-22.49). All subjects who had sunbathed or used tanning beds or lamps, skin tanning agents, tanning extenders and/or medical agents affecting skin pigmentation during the 60 days preceding the beginning of the study were excluded. The use of hormonal contraceptives within a month prior to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 81 publications
1
5
0
Order By: Relevance
“…Skin colour varies in all individuals, due to genetic variations, and it can be modified by exposure to ultraviolet (UV) radiation (Candille et al 2012). Skin colour can vary during puberty (Sitek et al 2012) and due to psychological stress (Sitek et al 2012). In humans melanin occurs in the stratum basale layer of the epidermis of skin, whereas chimpanzees store their melanin deeper in the dermis (Becker 1927).…”
Section: Skin Colour and Melanogenesismentioning
confidence: 99%
“…Skin colour varies in all individuals, due to genetic variations, and it can be modified by exposure to ultraviolet (UV) radiation (Candille et al 2012). Skin colour can vary during puberty (Sitek et al 2012) and due to psychological stress (Sitek et al 2012). In humans melanin occurs in the stratum basale layer of the epidermis of skin, whereas chimpanzees store their melanin deeper in the dermis (Becker 1927).…”
Section: Skin Colour and Melanogenesismentioning
confidence: 99%
“…It should be noted that this finding was based on student's perception and is self-reported and may not be equivalent to the actual stress measured using biomarkers because it is found that the level of perceived stress was negatively correlated with hair melanization. [ 20 ]…”
Section: Discussionmentioning
confidence: 99%
“…This process ensued once humans migrated toward more northerly latitudes and coincided with the advent of agricultural practices causing reduced nutritional vitamin D intake; importantly, it was mediated through changes in specific genes such as SLC24A5, SLC45A2, TYRP1 that led to significant skin depigmentation (Lucock, 2022). In particular, our group and others have characterized pigmentation diversity among adults and children in Poland using modern reflectometry measurements showing variation within a lighter skin color range (Candille et al, 2012;Siewierska-G orska et al, 2017;Sitek et al, 2013Sitek et al, , 2016Sitek et al, 2017).…”
Section: Studies Have Found Significant Vitamin D Deficiency In Northernmentioning
confidence: 92%